1811 N.J. Laws 225-26, An Act to Regulate Gun Powder Manufactories and Magazines within this State § 1 - (:unkn) unknown (General Publisher, 1811)
Required manufactories of gunpowder and storage magazines to be located away from populated areas.
--
Keywords: TRANSFER; MANUFACTURE & STORAGE OF GUNPOWDER